Influence of Sintering Additives on the Porous Structure and Mechanical Properties of Porous Alumina - Le, Minh Hai; Nguyen, Minh Duc; Dang, Quoc Khanh (Old Journal, 2017)
The aim of the present work is to investigate and to compare the influence of the two sintering additives Cr_2O_3 and TiO_2 on the porous structure and the mechanical properties of the sintered porous alumina. Alumina based porous ceramics were fabricated by sacrificial template technique via powder metallurgy route from alumina powder using ammonium bicarbonate (NH_4)HCO_3 as the pore former. The results showed that the use of sintering additives led to a remarkble enhancement of the bonding between alumina particles hence the strength of the alumina based porous ceramics. Between the two sintering additives, TiO_2 was more effective in aiding sintering (densification) of alumina than Cr_2O_3. Consequently, the sintered porous alumina using TiO_2 as sintering additive has a smaller pore size, 190±30 µm compared to 220±40 µm of that with Cr_2O_3, and lower porosity. The porosity of the sintered samples increased with the concentration of the pore-forming agents and reaches the highest value of 79.3% and 82.6% corresponding to TiO_2 and Cr_2O_3 used. The mechanical strength of the porous alumina varied inversely with porosity.